2017
DOI: 10.1016/j.ymthe.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Delivery of Single or Multiple Antigens in Tolerogenic Nanoparticles Using Peptide-Polymer Bioconjugates

Abstract: Polymeric nanoparticles (NPs) have demonstrated their potential to induce antigen (Ag)-specific immunological tolerance in multiple immune models and are at various stages of commercial development. Association of Ag with NPs is typically achieved through surface coupling or encapsulation methods. However, these methods have limitations that include high polydispersity, uncontrollable Ag loading and release, and possible immunogenicity. Here, using antigenic peptides conjugated to poly(lactide-co-glycolide), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 35 publications
4
103
0
Order By: Relevance
“…i.v.-administered NPs are thought to bind to circulating immune cells via scavenger receptors such as MARCO. NPs with a diameter of 500 nm were selected based on our previous work with autoimmune disease (30) and a greater internalization due in part to binding affinity for immune cells and flow patterns within the blood (12). Previous studies reported that neither resident microglia nor T lymphocytes express scavenger receptors such as MARCO (31), thus indicating that NPs target selectively circulating immune cells that would normally infiltrate a SCI.…”
Section: Discussionmentioning
confidence: 99%
“…i.v.-administered NPs are thought to bind to circulating immune cells via scavenger receptors such as MARCO. NPs with a diameter of 500 nm were selected based on our previous work with autoimmune disease (30) and a greater internalization due in part to binding affinity for immune cells and flow patterns within the blood (12). Previous studies reported that neither resident microglia nor T lymphocytes express scavenger receptors such as MARCO (31), thus indicating that NPs target selectively circulating immune cells that would normally infiltrate a SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Coupling antigens to spleen cells through ethylenecarbodiimide (ECDI) fixation has been shown to induce their apoptosis and treatments with these dead cell-peptide conjugates confers tolerance to the antigen in many preclinical models. This approach has been used to treat various diseases, including animal models of EAE and T1D ( 94 , 95 ). A similar strategy has been employed to target disease-relevant antigens to erythrocytes in vivo .…”
Section: Tolerogenic Nps That Provide Antigen Alone To Harness Naturamentioning
confidence: 99%
“…Previous studies using Ag-SP demonstrated the dependence of the spleen for tolerance induction [82], however, prophylactic tolerance induction by PLGA(Ag) particles was not solely dependent on the spleen [70]. Pearson et al developed Ag-polymer conjugate PLGA (acNP) particles that displayed modular Ag loading (up to 150 μg peptide per mg particle), low burst release, and minimally exposed surface Ag [94]. In vitro, acNPs were effective at inducing Tregs in a co-culture model of BMDCs, naïve OTII T cells, and TGF-p1.…”
Section: Apc Reprogrammingmentioning
confidence: 99%
“…(F) Corresponding cumulative clinical score for mice treated with particles (n = 5). Differences between disease courses of different treatment groups were analyzed for statistical significance using the Kruskal-Wallis test (one-way ANOVA non-parametric test) with Dunn's multiple comparisons test (p < 0.05) [94]. …”
Section: Figurementioning
confidence: 99%